Seasonal Variation of Pediatric Septic Arthritis in the United States: A PHIS Database Study. Issue 3 (28th March 2023) - Patankar, Aneesh G.; Coene, Ryan P.; Cook, Danielle L.; Feldman, Lanna; Hannon, Megan; Yen, Yi-Meng; Milewski, Matthew D.
Abstract : Background: The presence of seasonal patterns in pediatric septic arthritis cases is a common orthopaedic teaching. Seasonal variation has been seen in centers outside of the United States and with other inflammatory and infectious joint-related conditions within the country, but it is unknown if a seasonal pattern exists among different regions of the United States. The purpose of this study was to examine the seasonal variation of septic arthritis within specific regions across the United States. Methods: The Pediatric Health Information System database was queried for all patients 19 years or younger who were treated for septic arthritis. Data from 34 pediatric hospitals in the Pediatric Health Information System initiative were included. Centers were organized by geographical region, and season of presentation was determined using equinoxes/solstices. χ 2 tests were performed to detect seasonal differences in septic arthritis for the entire cohort and separated by geographical region. Proportion differences along with 95% CIs were provided. Results: Between 2016 and 2019, there were 5764 cases of septic arthritis. Median age at diagnosis was 6.2 years (range: 0 to 19.0 y). Each season contributed 24% to 25% of the total septic arthritis cases, and there were no significant differences detected between the 4 seasons ( P =0.66). There was no seasonal variation seen in the Midwest, South, or West ( P =0.71, 0.98, 0.36, respectively). However, there was seasonal variation in the Northeast ( P =0.05), with fall and summer having a higher percentage of cases (28%) than the winter (21%). Conclusions: This study showed no clear seasonal variation in septic arthritis in children across the United States using a national database of pediatric hospital centers. However, there is regional seasonal variation in the Northeast, which may relate to climate differences. With no clear seasonal variation across the United States, continued diligence is needed in diagnosing septic arthritis throughout the year. Level of Evidence: Prognostic II.